Structural diversity in binary superlattices from Au and γ-Fe2O3 nanocrystals: towards fine tuning of dipolar interactions. (6th June 2022) - Lee, Suyeon; Ngo, Anh-Tu; Lisiecki, Isabelle; Courty, Alexa
Abstract : Fabrication of NaZn13 binary superlattices composed of γ-Fe2 O3 and Au NPs and their magnetic properties compared to pure γ-Fe2 O3 NP superlattices. Abstract : Two cooperative and complementary components such as γ-Fe2 O3 /Au nanoparticles (NPs) are used to grow binary superlattices (BNSLs). The effects of different parameters including concentration ratio of colloidal solutions, effective size ratio of NPs, deposition temperature and type of solvent on the formation of BNSLs are discussed. A systematic study of the effect of these parameters is performed to determine the driving forces underlying the BNSL formation. We show that by using the same batch of particles, the control of the various parameters gives rise to a large diversity of crystalline structures. In addition, thanks to their long-range organization, the magnetic properties of γ-Fe2 O3 /Au NPs binary superlattices are studied by SQUID magnetometry and compared to those of pure γ-Fe2 O3 NPs superlattices. The γ-Fe2 O3 interparticle distance modulated by the insertion of Au NPs is shown to significantly impact their magnetic properties.